Semantic destiny of euphemisms: the nominative sphere of natural need satisfaction - Hadi, N. J. (Opción, 2019)
The article describes the main types of taboo unit transformation into euphemism in Arabic, the lexico-semantic evolution of euphemisms on the example of the nominative sphere of natural need satisfaction in ancient and modern Arabic via comparative qualitative research method. As a result, the need for defecation and urination requires you to go out into your personal space, and then sit down to defecate and urinate and finally remove the traces of defecation and urination. In conclusion, with linguistic and extralinguistic factors, euphemistic units can be subjected to the generalization or the narrowing of meanings like all words